A quantitative model of preferential evaporation and retention for atom probe tomography. (11th June 2014) - Takahashi, J.; Kawakami, K.
<x xml:space="preserve">Abstract</x> It is well known that the apparent concentration of a solute element in metal, detected by atom probe tomography analysis, depends on the measurement condition such as specimen temperature, pulse fraction, and pulse frequency. The dependence was qualitatively interpreted to be caused by preferential evaporation and retention in field evaporation. A quantitative physical model accounting for the preferential evaporation and retention was proposed herein for the first time. The proposed model was applied to a ferritic iron–copper (Fe–Cu) alloy for preferential evaporation and a ferritic iron–silicon (Fe–Si) alloy for preferential retention. The model explained the temperature dependence on the apparent concentration of the solute element and the unwindowed background noise in each alloy well, whereas the dependence of pulse fraction and pulse frequency was not completely explained. The cause of the difference between the experimental and calculated results based on the model was discussed. Copyright © 2014 John Wiley & Sons, Ltd.